PELAKSANAAN TANGGUNG JAWAB PENGANGKUTAN BARANG MELALUI LAUT DI PT. INDO PERDANA LINTASJAGAD BATAM DENGAN CV. JAYA RAYA - Pratomo, Bobby Farras; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The transport of goods in its implementation is preceded by agreement between the parties, namely the sender, the receiving party, and the third party as the introductory party. This freight deal is contained in a contract of carriage which includes the rights and obligations of each party in the process of delivery to the receipt of goods. This contract is very important considering the risks that will be encountered when the goods are in transit, the clause on the transport agreement must include also the rights and obligations of third parties. The purpose of this study is to know the rights and obligations in the agreement of transporting goods by sea at the transportation company PT. Indo Perdana Lintasjagad and constraints that occur in the implementation of goods transport by sea between PT.Indo Perdana Lintasjagad with CV. Jaya Raya.The type of this research is sociological law research that is research on the effectiveness of the current law while when viewed from the nature of this research is descriptive. This study uses primary data that is data obtained directly from the first source and direct observation conducted by the researcher into the field and secondary data that is the data that has been so.The results of this study are the rights and obligations in the sea freight transport agreement in the freight company PT.Indo Perdana Lintasjagad Batam embodied in legislation or delivery agreement of goods made by PT. IPL with CV. Jaya Raya. Rights and obligations between PT. IPL and CV. Jaya Raya is everything that must be met or must be accepted by PT. IPL and CV. Jaya Raya arising from a legally-established agreement. Constraints in the implementation of goods transport by sea between PT. Indo Perdana Lintasjagad with CV. Jaya Raya is a dense transport schedule followed by the number of existing customers and the delay of delivery of CV's belongings. Jaya Raya to Container Yard (CY), the occurrence of damage to the goods during the inspection process by the water police officers and at the time of bongkat loading by the ABK. To overcome this, done cooperation or sign contract with CV. Jaya Raya with a minimum contract period of one year.Keywords: responsibility, transportation, sea.